Book Review. Uricska Erna’s COVIDICTIONARY: Words and Phrases Related to the Global Pandemic (Papers in Arts and Humanities, 2021)
This unique work in its subject matter, genre and language was prepared during the first wave of the coronavirus epidemic. The theoretical background of the author’s research work is perfectly adjusted to Patyi’s “university triangle” model (“Nemzeti Közszolgálati Egyetem, Intézményfejlesztési Terv 2015–2020,” n.d.), which basically illustrates the functioning of a university in a triple system of the activities “research—education—curriculum development,” and Paavola and Hakkarainen’s trialogical model (2005), which—through the competence of cooperation—provides an opportunity todevelop students’ creativity, to keep their motivation at a high level, to develop competencies required by the labour market, and to implement experiential teaching–learning. A questionnaire survey was used with closed and open questions among students who have been learning English for law enforcement at the University of Public ServiceFaculty of Law Enforcement (hereinafter: UPS FLE) using the corpus-based dictionary method. The author’s acquaintances registered on Facebook social media platform were also involved in the research. The 96-page collection of words and phrases based on the theoretical background involves 403 English words, word phrases, neologisms and their definitions related to the coronavirus epidemic and COVID-19 situation during the first wave.
Keywords: covid dictionary; social networking sites; English for law enforcement; university triangle; trialogical learning